INTELLIGENT DECISION SUPPORT SYSTEMS MODELING USING ONTOLOGICAL APPROACH - Litvin, V. V. (Radio Electronics, Computer Science, Control, 2012)
The functioning of intelligent decision support systems with knowledge base based on ontology is investigated. Four types of intelligent agents are considered. Metrics for each of them is developed and used to determine the relevance of solutions proposed by the system.